Does managerial ability matter for the choice of seasoned equity offerings? - Pratheepkanth, P.; Dang Man.; Henry, D.; Pratheepkanth, P.; Mamun, Md.A.L. (My University, 2019)
We provide evidence that managerial ability is positively and significantly related to the issuance method decision of seasoned equity offerings (SEOs) in the U.S. market. Our result is robust after controlling for various internal and external governance mechanisms, addressing the problem of endogeneity, and adopting a number of alternative specifications. We further find that the impact of managerial ability on the SEO issuance choice is stronger for firms with higher information asymmetry, CEO duality and weaker governance settings. Overall, our study supports the notion that higher managerial ability is perceived as a positive quality certification on firm information environments.
Keywords: Seasoned equity offerings; Managerial ability; Information asymmetry; CEO duality; Institutional investors